ANALISIS PERBEDAAAN AVERAGE ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SESUDAH PERISTIWA DIVIDEN TUNAI PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2014 – 2017 - Azyyati Yusrina; Puji Sucia Sukmaningrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to find out and explain the market reaction caused by the corporate action announcement in the form of dividend cash made by issuers registered in the Jakarta Islamic Index for the period of 2014 to 2017. The object of research is issuers who carry out activities on the announcement of Cash Devidend in the period of observation that are registered in the Jakarta Islamist Index which has been determined based on certain criteria (purposive sampling). There are 17 issuers with a total of 91 being the research sample. The observation period consists of 60 days estimated period, 10 days before the cume date and 10 days after the cume date. The focus of the research is to see the reaction shown by changes in Average Abnormal Return and Trading Volume Activity by using paired sample t-test for trading volume activity variables and Wilcoxon sign-rank test for abnormal return variables. Processing data using Stata ver statistical tools 14 by setting a significant level of 5%. The results showed that there were significant differences in Average Abnormal Return before and after the announcement and there were no differences in the Trading Volume Activity before and after the announcement.Keywords: event study, cash deviden, Average Abnormal Return, Trading Volume Activity